A high-quality chromosomal genome assembly of Diospyros oleifera Cheng - Suo, Yujing (Gigascience, 2020)
BACKGROUND: Diospyros oleifera Cheng, of the family Ebenaceae, is an economically important tree. Phylogenetic analyses indicate that D. oleifera is closely related to Diospyros kaki Thunb. and could be used as a model plant for studies of D. kaki. Therefore, development of genomic resources of D. oleifera will facilitate auxiliary assembly of the hexaploid persimmon genome and elucidate the molecular mechanisms of important traits. FINDINGS: The D. oleifera genome was assembled with 443.6 Gb of raw reads using the Pacific Bioscience Sequel and Illumina HiSeq X Ten platforms. The final draft genome was ∼812.3 Mb and had a high level of continuity with N50 of 3.36 Mb. Fifteen scaffolds corresponding to the 15 chromosomes were assembled to a final size of 721.5 Mb using 332 scaffolds, accounting for 88.81% of the genome. Repeat sequences accounted for 54.8% of the genome. By de novo sequencing and analysis of homology with other plant species, 30,530 protein-coding genes with an average transcript size of 7,105.40 bp were annotated; of these, 28,580 protein-coding genes (93.61%) had conserved functional motifs or terms. In addition, 171 candidate genes involved in tannin synthesis and deastringency in persimmon were identified; of these chalcone synthase (CHS) genes were expanded in the D. oleifera genome compared with Diospyros lotus, Camellia sinensis, and Vitis vinifera. Moreover, 186 positively selected genes were identified, including chalcone isomerase (CHI) gene, a key enzyme in the flavonoid-anthocyanin pathway. Phylogenetic tree analysis indicated that the split of D. oleifera and D. lotus likely occurred 9.0 million years ago. In addition to the ancient γ event, a second whole-genome duplication event occurred in D. oleifera and D. lotus. CONCLUSIONS: We generated a high-quality chromosome-level draft genome for D. oleifera, which will facilitate assembly of the hexaploid persimmon genome and further studies of major economic traits in the genus Diospyros.